Analisis Mitigasi Risiko Pembiayaan Koperasi Syariah - Nanang Sobarna (J-Coop : Journal of Co-operative, 2026)
Sharia cooperatives play a strategic role in enhancing member welfare by providing financing services based on Sharia principles. However, these financing activities are subject to various risks—particularly the risk of Non-Performing Financing (NPF)—which can impact the cooperative's stability and sustainability. This study aims to analyze the concept of Sharia financing risk, its underlying factors, and risk mitigation strategies applicable to Sharia cooperatives. A qualitative approach utilizing library research was employed. Data were gathered through a review of secondary sources, including scholarly articles, books, legislation, fatwas from the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI), and official publications regarding risk management and Sharia cooperatives. Analysis was conducted descriptively through the identification, classification, synthesis, and interpretation of relevant literature. The findings indicate that Sharia financing risk encompasses not only default risk but also Sharia compliance risk, operational risk, legal risk, liquidity risk, market risk, and reputational risk. These risks are influenced by internal factors—such as weak financing analysis, limited human resource competence, and member moral hazard—as well as external factors, including changes in economic conditions, regulations, and business environment dynamics. Effective financing risk mitigation is achieved through the application of the 5C + 1S principles (character, capacity, capital, collateral, condition of the economy, and Sharia compliance), financing portfolio diversification, enhanced member education, continuous financing monitoring via early warning systems, and financing restructuring based on Sharia-compliant principles of consultation and fairness. These strategies are expected to reduce NPF levels, improve financing portfolio quality, strengthen member trust, and support the sustainability of Sharia cooperatives.